2021
DOI: 10.1016/j.ijporl.2021.110861
|View full text |Cite
|
Sign up to set email alerts
|

Safety of elective paediatric surgery during the coronavirus disease 2019 pandemic

Abstract: Introduction Corona-virus Disease 2019 (COVID-19) has had a huge impact on the delivery of healthcare worldwide, particularly elective surgery. There is a lack of data regarding risk of postoperative COVID-19 infection in children undergoing elective surgery, and regarding the utility of pre-operative COVID-19 testing, and preoperative “cocooning” or restriction of movements. The purpose of this present study was to examine the safety of elective paediatric Otolaryngology surgery during the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These two studies did not include matched controls and were based solely on observed post-operative complication rates among infected children. Kavanagh et al did not identify any pulmonary complications in infected children who underwent surgery in a two-month time frame 16 . However, Saynhalath et al concluded increased risk for pulmonary complications in infected children in a study which included matched controls 11 .…”
Section: Discussionmentioning
confidence: 97%
“…These two studies did not include matched controls and were based solely on observed post-operative complication rates among infected children. Kavanagh et al did not identify any pulmonary complications in infected children who underwent surgery in a two-month time frame 16 . However, Saynhalath et al concluded increased risk for pulmonary complications in infected children in a study which included matched controls 11 .…”
Section: Discussionmentioning
confidence: 97%